Sub-optimal orbital maneuvers for artificial satellites - Vaz, Bruno Nunes [UNESP]; Prado, Antonio Fernando Beratachini De Almeida (My University, 2008)
The determination of a specific orbit and the procedure to calculate orbital maneuvers for artificial satellites are problems of extreme importance in the study of orbital mechanics. Therefore, the transferring problem of a spaceship from one orbit to another, and the attention to this subject has increased during the last years. Many applications can be found in several space activities, for example, to put a satellite in a geostationary orbit, to change the position of a spaceship, to maintain a specific satellite's orbit, in the design of an interplanetary mission, and others. The orbit and the general data of the Brazilian Satellite SCD-1 (Data Collecting Satellite) will be used as example in this paper. It is the first satellite developed entirely in Brazil, and it remains in operation to this date. SCD-1 was designed, developed, built, and tested by Brazilian scientists, engineers, and technicians working at INPE (National Institute for Space Research) and in Brazilian Industries. During its lifetime we will study its orbital behavior and we will perform some orbital maneuvers that could be necessary, being this one either an orbital transferring, or just to make periodical corrections. The purpose of the transferring problem is to change the position, velocity and the satellite's mass to a new pre-determined state. This transfer can be totally linked (in the case of Rendezvous) or partially free (free time, free final velocity, etc). In the global case, the direction, the orientation and the magnitude of the thrust to be applied must be chosen, respecting the equipment's limit. In order to make this transferring, either sub-optimal or optimal maneuvers may be used. In the present study, only the sub-optimal will be shown, since we want to study an algorithm for this type of maneuver. Hence, this method will simplify the direction of thrust application, to allow a fast calculation that may be used in real time, with a very fast processing. The thrust application direction to be applied will be assumed small and constant, and the purpose of this paper is to find the time interval that the thrust is applied. This paper is basically divided into three parts: during the first one the sub-optimal maneuver is explained and detailed, the second presents the Satellite SCD-1, and finally the last part shows the results using the sub-optimal maneuver applied to the Brazilian Satellite.
Keywords: Astrodynamics; Brazilian Satellites; Orbital Maneuvers; Space Trajectories; Spatial Mechanics